Clinical Decision Support in the Management of Patients With Suspected Ebola Infection. (10th April 2015) - Landman, Adam B.; Goralnick, Eric; Teich, Jonathan M.
Abstract: Patients with suspected public health threats, such as Ebola, must be quickly identified and isolated on presentation to health care facilities. Patients can be screened by intake staff or other health care providers; however, perfect compliance is difficult to achieve. Well-designed, carefully placed clinical decision support (CDS) within the electronic health record can be a reliable partner in helping to rapidly identify, isolate, and care for patients with suspected Ebola infection and other emerging public health threats. We describe how different types of CDS can be applied in the clinical workflow and share how we implemented CDS to force Ebola screening upon patient presentation to our emergency department. ( Disaster Med Public Health Preparedness. 2015;9:591–594)